2017
DOI: 10.21577/0100-4042.20170060
|View full text |Cite
|
Sign up to set email alerts
|

A novel rhodamine-based fluorescence chemosensor containing polyether for mercury (II) ions in aqueous solution

Abstract: publicado na web em 01/06/2017 A novel rhodamine-based Hg 2+ chemosensor P2 containing polyether was readily synthesized and investigated, which displayed high selectivity and sensitivity for Hg 2+ . Because of good water-solubility of polyther, the rhodamine-based chemosensor containing polyether can be used in aqueous solution. The sensor responded rapidly to Hg 2+ in pure water solutions with a 1:1 stoichiometry. Meanwhile, it indicated excellent adaptability and also the responsiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…Considering the collective results, the chelation of CP2 with Hg 2+ was favorable via the "O" atom of the carbonyl group and the amino "N" atom of the rhodamine unit owing to the high affinity of Hg 2+ ions as a soft acid for N and O atoms (Figure 5A). 45 This showed that Hg 2+ coordinated with the • N−O • receptor under a suitable geometry conformation and resulted in a spirolactam ring-opening. 56,61 Moreover, we checked the 1 H NMR spectra of CP2 after the addition of Hg 2+ for further verification of the sensing mechanism but did not find any significant change in chemical shifts (data not shown here).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Considering the collective results, the chelation of CP2 with Hg 2+ was favorable via the "O" atom of the carbonyl group and the amino "N" atom of the rhodamine unit owing to the high affinity of Hg 2+ ions as a soft acid for N and O atoms (Figure 5A). 45 This showed that Hg 2+ coordinated with the • N−O • receptor under a suitable geometry conformation and resulted in a spirolactam ring-opening. 56,61 Moreover, we checked the 1 H NMR spectra of CP2 after the addition of Hg 2+ for further verification of the sensing mechanism but did not find any significant change in chemical shifts (data not shown here).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Additionally, CP2 exhibited a feeble absorption band at 560 nm, which could be credited to the existence of a minute amount of the ring-opened amide form of rhodamine in the pendant (Figure S8). 45 Before the implication of CP2 as a sensor, we have investigated the stability of the polymeric sensor in water with respect to time. For this, the absorption spectra of an aqueous solution of CP2 (1 mg/mL) were recorded at different time intervals from 0 to 24 h at pH 7.0 (Figure S9).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Colorimetric sensors such as triazine, coumarin, quinolone, rhodamine, and chromenylium-cyanine have been designed for detection of the transition metal ions in aqueous media (Aksuer et al, 2011Du et al, 2017Voutsadaki et al, 2010;;Wei et al, 2016). Hydroxybenzaldehyde Schiff bases derived from Rhodamine B, one of the most used probe structure, was enables Cu 2+ sensing via coordination of transition metal ion through phenolic oxygen and imine nitrogen atoms of the sensor because of its large association constant (Li et al, 2015;Tang et al,2011;Xiang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%